2018
DOI: 10.1523/jneurosci.2915-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

The Avian Basal Ganglia Are a Source of Rapid Behavioral Variation That Enables Vocal Motor Exploration

Abstract: The basal ganglia (BG) participate in aspects of reinforcement learning that require evaluation and selection of motor programs associated with improved performance. However, whether the BG additionally contribute to behavioral variation ("motor exploration") that forms the substrate for such learning remains unclear. In songbirds, a tractable system for studying BG-dependent skill learning, a role for the BG in generating exploratory variability, has been challenged by the finding that lesions of Area X, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 54 publications
7
57
0
Order By: Relevance
“…In contrast, failure signals may promote network states that will generate behavioral variation on the next trial. If failure signals are generic error messages, the effects could be to put the PT network into a state that allows more explorations on future trials, analogous to a strategy thought to be used in songbird learning (Kojima et al, 2018). On the other hand, if the failure outcome signals provide information about the nature of the error, they might influence the network to produce a more specific adaptive correction.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, failure signals may promote network states that will generate behavioral variation on the next trial. If failure signals are generic error messages, the effects could be to put the PT network into a state that allows more explorations on future trials, analogous to a strategy thought to be used in songbird learning (Kojima et al, 2018). On the other hand, if the failure outcome signals provide information about the nature of the error, they might influence the network to produce a more specific adaptive correction.…”
Section: Discussionmentioning
confidence: 99%
“…When a male zebra finch sings its courtship song to a female of interest, song is highly stereotyped and tonic levels of dopamine (DA) are increased in Area X, a vocal motor basal ganglia nucleus capable of regulating song variability 48 . Yet when males practice alone, song is highly variable and tonic DA levels are decreased in Area X 4, 9 .…”
Section: Figurementioning
confidence: 99%
“…Yet when males practice alone, song is highly variable and tonic DA levels are decreased in Area X 4, 9 . Blockade or disruption of striatal DA signaling eliminates the social context-dependent transition between ‘practice’ and female-directed ‘performance’ modes 10, 11 , suggesting that tonic DA levels actively regulate ongoing vocal variability 5, 7, 8, 12 .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The amount of this 73 compensation became larger when distributions of original and shifted FF variations are more overlapped 74 (Sober and Brainard, 2012;Kuebrich and Sober, 2015), linking the wider variability with the greater vocal 75 adaptations. It has also been shown that temporal patterns of FF fluctuation within a brief sound element guide 76 to keep and improve the song quality (Charlesworth et al, 2011;Kojima et al, 2018). Intriguingly, the vocal 77 variability in birdsongs is not simply due to the intrinsic noise in the peripheral motor system, but a certain 78 amount of them is 'actively' generated by a dedicated circuit that is required for song learning ( the active generation of variability in the motor processes is likely to suit to the adaptation-related motor 83 exploration (Dhawale et al, 2017).…”
Section: Introduction 55mentioning
confidence: 99%